Sugarcane Bagasse Pyrolysis in a Carbon Dioxide Atmosphere with Conventional and Microwave-Assisted Heating - Lin, Bo-Jhih; Chen, Wei-Hsin (Frontiers in Energy Research, 2015)
Pyrolysis is an important thermochemical method to convert biomass into bio-oil. In this study, the pyrolysis of sugarcane bagasse in a CO2 atmosphere under conventional and microwave-assisted heating is investigated to achieve CO2 utilization. In the microwave pyrolysis, charcoal is used as the microwave absorber to aid in pyrolysis reactions. The results indicate that the yields of pyrolysis products are greatly influenced by the heating modes. In the conventional heating, the prime product is bio-oil and its yield is in the range of 51-54 wt%, whereas biochar is the major product in microwave-assisted heating and its yield ranges from 61 to 84 wt%. Two different absorber blending ratios of 0.1 and 0.3 are considered in the microwave pyrolysis. The solid yield decreases when the absorber blending ratio decreases from 0.3 to 0.1, while the gas and liquid yields increase. This is attributed to more energy consumed for bagasse pyrolysis at the lower blending ratio. Hydrogen is produced under the microwave pyrolysis and its concentration is between 2 and 12 vol%. This arises from the fact that the secondary cracking of vapors and the secondary decomposition of biochar in an environment with microwave irradiation is easier than those with conventional heating.